2003
DOI: 10.1111/1475-6773.00175
|View full text |Cite
|
Sign up to set email alerts
|

Using Claims Data to Examine Mortality Trends Following Hospitalization for Heart Attack in Medicare

Abstract: Prediction models based on claims-derived demographics and morbidity profiles can be extremely accurate. While one-year post-AMI mortality in Medicare may not be worsening, outcomes appear not to have continued to improve as they had in the prior decade. Rich morbidity information is available in claims data, especially when longitudinally tracked across multiple settings of care, and is important in setting performance targets and evaluating trends.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
69
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(71 citation statements)
references
References 2 publications
1
69
1
Order By: Relevance
“…15 The method of creation and validation of AHRQ-CCS was previously published. [19][20][21][22][23] AHRQ-CCS disease categories have been widely used in numerous publications to identify comorbidities and outcomes, [24][25][26][27][28][29] predict mortality, 30,31 and estimate utilization and costs. [32][33][34][35] AHRQ-CCS disease categories are recognized by the Department of Defense Military Health System and are incorporated into Tricare data as an industry standard.…”
Section: Discussionmentioning
confidence: 99%
“…15 The method of creation and validation of AHRQ-CCS was previously published. [19][20][21][22][23] AHRQ-CCS disease categories have been widely used in numerous publications to identify comorbidities and outcomes, [24][25][26][27][28][29] predict mortality, 30,31 and estimate utilization and costs. [32][33][34][35] AHRQ-CCS disease categories are recognized by the Department of Defense Military Health System and are incorporated into Tricare data as an industry standard.…”
Section: Discussionmentioning
confidence: 99%
“…37 DCGs are highly predictive of mortality for Medicare beneficiaries with myocardial infarction 38 and cancer, 39 and because they capture so many conditions, they may be particularly useful in differentiating among women whose Charlson score is 0. We calculated summary DCG scores (categorized in quartiles; excluding breast cancer codes) based on the 12 months before death.…”
Section: Covariatesmentioning
confidence: 99%
“…22 Nevertheless, numerous prior studies have used administrative data to measure quality 23,24 including several VA studies. [25][26][27] Moreover, in a comparison of statistical models based on administrative data and clinical data from medical records, Krakauer et al 28 found that administrative data are satisfactory for characterizing variations in hospital mortality rates, whereas Ash et al 29 concluded that prediction models based on claims data can be accurate. Additionally, our inclusion of a laboratory-based measure addresses some of the limitations of administrative data regarding unmeasured severity of illness.…”
Section: Discussionmentioning
confidence: 99%